EKSPLORASI KESESUAIAN PELAKSANAAN PRAKTIK KERJA LAPANGAN (PKL) DENGAN KOMPETENSI KEAHLIAN BISNIS RITEL SISWA SMK NEGERI 1 BATANG HARI - Septi Liana, Ainia; Arpizal; Dwi Rayana Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the discrepancy between the locations and activities of the industrial training program and the students’ competencies, resulting in practical experiences that do not fully support their readiness for the workforce. The study employed a descriptive qualitative approach through interviews, observations, and documentation. The research informants consisted of students, supervising teachers, the vice principal for curriculum, the head of the vocational program, and representatives from the business/industrial sector. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the internship program is proceeding fairly well; however, its alignment with retail business competencies is not yet optimal. Alignment is evident in the aspects of customer service and communication, whereas inventory management, the use of digital cash register systems, and digital marketing have not been maximized. Factors influencing these conditions include the limited availability of relevant PKL sites and the suboptimal implementation of digital work systems at the PKL sites. Therefore, enhanced collaboration between schools and the business/industrial sector is necessary to ensure that the implementation of PKL aligns with student competencies, thereby improving graduates’ skills and work readiness.